Pengaruh Ekstrak Etanol Belimbing Wuluh (Averrhoa bilimbi Linn.) dengan Variasi Dosis terhadap Kadar Testosteron Bebas Tikus Putih (Rattus norvegicus) - Jannah, Nur Zahratul; Doewes, Muchsin; Kisrini, . (Nexus Kedokteran Translasional, 2013)
Background: Belimbing wuluh (Averrhoa bilimbi Linn.) contains apigenin and luteolin as natural flavonoids, and antioxidants that may increase testosterone levels. Apigenin and luteolin increase testosterone levels by enhancing StAR (Steroidogenic Acute Regulatory) activity. Antioxidant protects cell from oxidative stress caused by ROS (Reactive Oxygen Species). This study aimed to evaluate the effect of variation dosage of Belimbing Wuluh (Averrhoa bilimbi Linn.) ethanolic extract on free testosterone levels in rats (Rattus norvegicus) Methods: This  was a pure experimental study with randomized post test only controlled group design. Samples were 24 male Wistar strain rats, 8-10 weeks aged and weighted ± 200 g on average. Samples were randomly divided into 4 groups, each group consists of six rats. Group K were given aquadest for 14 days. Group P1, P2, P3 were given ethanolic extract of belimbing wuluh orally at dose 57 mg/200 g body weight of rats, 114 mg/200 g body weight of rats, and 228 mg/200 g body weight of rats for 14 days. At 15th, blood were drawn from retroorbitalis plexus using microtubuler tube and free testosterone level were measured. Free testosterone levels of rats were measured by using ELISA (Enzyme-linked Immunosorbent Assay) method. Data were analyzed using one-way ANOVA test (α = 0.05). Results: Mean free testosterone levels in group K was 2.40 ± 2.02 ng/ml; in group P1 was 1.76 ± 1.01 ng/ml, in group P2 was 1.58 ± 0.53 ng/ml and in group P3 was 1.68 ± 0.64 ng/ml. Results for one-way ANOVA test showed no mean different (p=0.642). Conclusions: There were no effect between variation dosage of belimbing wuluh (Averrhoa bilimbi Linn.) ethanolic extract on free testosterone level in rats (Rattus norvegicus). Keywords: Averrhoa bilimbi Linn. extract, flavonoid, free testosterone level